PENERAPAN ASAS PARI PASSU PRO RATA PARTE DALAM PERJANJIAN KREDIT SINDIKASI TERHADAP DEBITUR PAILIT - , ULIL AFWA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to answer two problems associated with the implementation of pari passu pro rata parte principle in a syndicated loan agreement to bankrupt debtor. First, to determine the position of each creditor to collateral in syndicated loans when it come to bankruptcy